Strong and weak plasma response to dietary carotenoids identified by cluster analysis and linked to beta-carotene 15,15'-monooxygenase 1 single nucleotide polymorphisms - Wang, Thomas T.Y; Edwards, Alison J; Clevidence, Beverly A (The Journal of nutritional biochemistry, 2013)
The mechanisms as well the genetics underlying the bioavailability and metabolism of carotenoids in humans remain unclear. To begin to address these questions, we used cluster analysis to examine individual temporal responses of plasma carotenoids from a controlled-diet study of subjects who consumed carotenoid-rich beverages. Treatments, given daily for 3 weeks, were watermelon juice at two levels (20-mg lycopene, 2.5-mg β-carotene, n=23 and 40-mg lycopene, 5-mg β-carotene, n=12) and tomato juice (18-mg lycopene, 0.6-mg β-carotene, n=10). Cluster analysis revealed distinct groups of subjects differing in the temporal response of plasma carotenoids and provided the basis for classifying subjects as strong responders or weak responders for β-carotene, lycopene, phytoene and phytofluene. Individuals who were strong or weak responders for one carotenoid were not necessarily strong or weak responders for another carotenoid. Furthermore, individual responsiveness was associated with genetic variants of the carotenoid metabolizing enzyme β-carotene 15,15'-monooxygenase 1. These results support the concept that individuals absorb or metabolize carotenoids differently across time and suggest that bioavailability of carotenoids may involve specific genetic variants of β-carotene 15,15'-monooxygenase 1.